THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES (SMMA) ON THE PURCHASE INTEREST IN SERVICES AND PRODUCTS CREATED BY INMATES - Tarigan, Ade Fahrezi; Pangestuti, Naniek (Universitas Nusa Cendana, 2025)
The era of globalization has made social media the most widely used platform by the public. Therefore, Correctional Institutions must utilize it to increase Non-Tax State Revenue (PNBP). Theoretically, Social Media Sales Activities (APMS) can increase purchase intention by considering five factors: Entertainment, Interaction, Trendiness, Customization, and Advertisement. The research problem in this study is whether social media sales activities (APMS) influence the purchase intention of services and products created by inmates at the Class IIA Rantauprapat Correctional Institution. This study aims to determine the influence of social media sales activities (APMS) on the purchase intention of services and products created by inmates at the Class IIA Rantauprapat Correctional Institution. The conclusion drawn from this research is that there is a positive and significant relationship between Social Media Marketing Activities (APMS) and the Purchase Intention of services and products created by inmates at the Class IIA Rantauprapat Correctional Institution. Keywords: Social Media Sales Activities (APMS); Purchase Intention; Correctional Sales